The Compensation and Work Motivation of Madrasah Tsanawiyah Teachers: A Correlational Analysis - Cholizah, Syfa Nurul; Juhji, Juhji; Mansur, Mansur (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
This study examines how Madrasah Tsanawiyah teachers' motivation for their work and pay interact. A survey method was employed in this study. Thirty teachers from Madrasah Tsanawiyah Cibeber Lebak Regency participated in this study. A Likert scale questionnaire with five verified response alternatives was used as the study tool. The teacher used a printed copy of the instrument to collect the instruments. According to the study, teacher work motivation is 74.80% in the very good category, and compensation is in the very good category with an achievement level of 74.78%. The correlation coefficient r is 0.70, indicating a significant and sufficient connection. Of the elements influencing teacher job motivation, 49% are related to compensation, and the remaining 51% are determined by additional factors not included in this research and which need more investigation. The study's findings indicate that remuneration and work motivation are significantly correlated. The study's conclusions suggest boosting teachers' enthusiasm at work by giving them more money through various supportive initiatives.